A concept of microwave photonic sensor systems based on addressed fiber Bragg gratings. (March 2020) - Zh Sakhabutdinov, A; Morozov, O G; Morozov, G A; Sh Misbakhov, R; Kuznetsov, A A; Nureev, I I
Abstract: The main drawback of the modern microwave photonic sensor systems is the absence of addressable fiber optic sensors, as a rule, based on fiber Bragg gratings, which leads to the need to build complex sensing systems and interrogators that are tuned to different wavelengths or combined into groups according to the common central wavelength. We proposed addressed fiber Bragg gratings, which structures can be realized in two variants: with two symmetrical phase π-shifts in one grating (2π-AFBG) or two serial gratings with different Bragg wavelengths (2λ-AFBG). Their common feature is difference frequency between two phase shifts or two gratings, which is lying in microwave range and defining its address, wherein addressed gratings have the same Bragg or central wavelength. So, their interrogation can be realized in microwave range by evaluation of envelope characteristics of beating signal on addressed frequency components. A new microwave photonic sensor systems class is called "MicroWave Photonic Sensor Systems based on Addressed Fiber Bragg Gratings". The concept of new class sensor systems is presented. The sets of analysis and synthesis problems, measuring level design for point, few sensor and multi-sensor variants, and principle of joint field of multiplexed sensors construction for system are considered. When implemented, the interrogation speed can be increased to hundreds of MHz, the resolution is up to units of Hz, which is determined by the parameters of microwave (not optical) processing, cost of system, its exploitation and design complexity are drastically decreased.